Revealing Media Trials in Indian Law: Critical Analysis - Basu, Arnab (Journal of Social Science and Humanities, 2024)
This article delves into the intricate phenomenon of media trials in Indian jurisprudence, offering a critical analysis of their impact on the nation’s legal landscape and society at large. It explores the evolution of media trials, examining their historical roots and transformation in the digital age. The article investigates the constitutional framework governing media freedom and the delicate balance it strikes with the right to a fair trial. It scrutinizes the ethical considerations and mechanisms of accountability within media trials, highlighting the challenges of sensationalism and ethical lapses. Furthermore, it elucidates the legal constraints imposed on media conduct, encompassing contempt of court, defamation, and privacy rights. The article also evaluates the recommendations put forth in the Law Commission’s 200th report and discusses landmark verdicts that have shaped the discourse around media trials. It concludes with concrete suggestions for fostering responsible journalism, mitigating undue media influence, and preserving the principles of justice and democracy in the digital age, while also acknowledging the role of social media in shaping media trials. This article provides a comprehensive overview of media trials in India, shedding light on their complexities and offering insights for a more balanced and equitable legal landscape.